Ergonomic intervention in fertilizer manufacturing company - Mohammad Azizol Abdul Aziz (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The purpose of this study is to study is solve the problem of worker lifting the fertilizer bag at Fertilizer Manufacturing company. This used questionnaies Nordic as questionnaiesor structured interviews. However, a higher frequency of musculoskeletal problem reported when the questionnaies was administered as part of the study focused on issue of muscle and work factors. In addition,